History Curriculum Policy of Senior High School during Sukarno Era - Zulkarnain, Zulkarnain (Paramita: Historical Studies Journal, 2020)
This article aims to investigate the history curriculum policy of senior high school during the Sukarno era. The method used is qualitative research by using the historical approach. Also, this research used document study as the primary method. A document study was conducted to both the primary and secondary sources for the source triangulation. Additionally, the complementary approach used interviews with several practitioners and academics, including the practitioners of the Indonesia history curriculum. Data analysis used an interactive analysis model. The results show that during 1945-1951, the history curriculum of senior high school still used AMS (Algemene Middelbare School) curriculum as the inheritance from the Dutch Indies era, so it is directed to the political policy, and the materials are clearly oriented to politics, doctrine, national ideology. The philosophical foundation of history curriculum policy in senior high school during the Sukarno Era is based on Pancasila and UUD 1945. But its implementation refers to government politics and essentialism and perennialism philosophy. The position of history subject in senior high school during the Sukarno era has a strategic role in creating historical awareness and nationalism. However, Manipol USDEK indoctrination was very visible.Ã‚Â Ã‚Â Artikel ini bertujuan untuk menyelidiki kebijakan kurikulum sejarah SMA pada era Sukarno. Metode yang digunakan adalah penelitian kualitatif dengan menggunakan pendekatan sejarah. Selain itu, penelitian ini menggunakan studi dokumen sebagai metode utama. Studi dokumen dilakukan pada sumber primer dan sekunder untuk triangulasi sumber. Selain itu, pendekatan komplementer menggunakan wawancara dengan beberapa praktisi dan akademisi, termasuk praktisi kurikulum sejarah Indonesia. Analisis data menggunakan model analisis interaktif. Hasil penelitian menunjukkan bahwa selama tahun 1945-1951, kurikulum sejarah sekolah menengah atas masih menggunakan kurikulum AMS (Algemene Middelbare School) sebagai warisan dari jaman Hindia Belanda, sehingga mengarah pada kebijakan politik, dan materi yang jelas berorientasi pada politik, doktrin, ideologi nasional. Landasan filosofis kebijakan kurikulum sejarah di Sekolah Menengah Atas pada masa Sukarno berpijak pada Pancasila dan UUD 1945. Namun implementasinya mengacu pada filosofi politik pemerintahan dan esensialisme dan perenialisme. Kedudukan mata pelajaran sejarah di sekolah menengah atas pada era Soekarno memiliki peran strategis dalam menciptakan kesadaran sejarah dan nasionalisme. Namun, indoktrinasi Manipol USDEK sangat terlihat.Ã‚Â